Painéis de pínus e bagaço de cana empregando-se dois adesivos para uso na construção civil - Buzo, Ana Laura Soler Cunha [UNESP]; Sugahara, Estéfani Suana [UNESP]; Silva, Sérgio Augusto De Mello Da [UNESP]; Morales, Elen Aparecida Martines [UNESP]; Azambuja, Maximiliano Dos Anjos [UNESP] (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2019)
This research project aimed to produce and evaluate particleboard using sugarcane bagasse (Saccharum officinarum) and pínus (Pinus taeda; Pinus elliotti) particles by comparing the efficiency of the two adhesives: urea-formaldehyde and polyurethane adhesive based on castor oil. The panels were made with 60% of pine wood particles, and 40% of sugarcane bagasse particles. The physical properties (density, moisture content and thickness swelling after 24h in water immersion), and mechanical properties (modulus of elasticity, modulus in static bending, and perpendicular traction to faces) of the panels were evaluated according to the use requirements set by the standards NBR 14810-1 (ABNT, 2013a), NBR 14810-2 (ABNT, 2013b) and EN-312. Panels produced with PU-Castor presents higher efficiency and compatibility with the physical and mechanical requirements of Brazilian and European standards for panels of type P6 (structural panels for use under severe load conditions in dry conditions). Panels produced with urea-formaldehyde are compatible with panels classified as P2 (non-structural panels for use in dry conditions). The results achieved proved the effectiveness of the panels produced, which can be used in the furniture and construction industries.

O presente trabalho objetivou produzir e avaliar painéis aglomerados empregando-se partículas de bagaço de cana-de-açúcar (Saccharum officinarum) e de pínus (Pinus taeda, Pinus elliottii), comparando-se a eficiência de dois adesivos, ureia-formaldeído e poliuretano derivado do óleo de mamona. Os painéis foram preparados com 60% de partículas de pínus e com 40% de partículas de bagaço de cana. Foram avaliadas propriedades físicas (densidade, teor de umidade e inchamento em espessura após 24 h de imersão em água) e mecânicas (módulo de elasticidade, módulo de resistência à flexão estática e tração perpendicular às faces) dos painéis de acordo com os requisitos de uso das normas NBR 14810-1 (ABNT, 2013a), NBR 14810-2 (ABNT, 2013b) e EN-312. Os painéis confeccionados com poliuretano de mamona apresentaram maior eficiência, sendo compatíveis com os requisitos físicos e mecânicos das normas brasileiras e europeia para painéis do tipo P6 (painéis estruturais para uso em condições severas de carga, em condições secas). Os painéis produzidos com ureia-formaldeído são compatíveis com painéis classificados como P2 (painéis não estruturais para uso em condições secas). Dessa forma, os resultados alcançados comprovaram a eficácia dos painéis produzidos, que podem ser empregados nas indústrias moveleira e da construção civil.
Pine and sugarcane bagasse particleboard using two adhesives for use in the construction industry
Keywords: Agglomerated panels; Polyurethane based on castor oil; Urea-formaldehyde polymer; Physical-mechanical properties; Painéis aglomerados; Poliuretano derivado do óleo de mamona; Ureia-formaldeído; Propriedades físico-mecânicas